2020
DOI: 10.3390/app10165403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Handgrip Strength on Clinical Outcomes of Patients with Hepatocellular Carcinoma Treated with Lenvatinib

Abstract: Previous studies have reported prognostic factors for hepatocellular carcinoma (HCC) patients receiving lenvatinib; however, no studies have evaluated the effects of both handgrip strength and skeletal muscle mass on the clinical outcomes. Therefore, this retrospective study investigated the individual effect of handgrip strength, skeletal muscle mass, and sarcopenia on clinical outcomes of 53 HCC patients treated with lenvatinib. Before receiving lenvatinib, handgrip strength and skeletal muscle index (SMI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The first report on the relationship between skeletal MM and clinical outcome was described in 2020, when Uojima et al [ 37 ] demonstrated that low MM was significantly associated with worse time to treatment failure and worse OS. Thereafter, two reports were published at the same time in which skeletal muscle depletion was not found associated with OS, unlike in a previous report [ 17 , 18 ]. In contrast, Hiraoka et al [ 38 ] recently reported that low MM was a significant prognostic factor.…”
Section: Impact Of Skeletal MM On Survival Among Patients Treated Wit...mentioning
confidence: 96%
See 4 more Smart Citations
“…The first report on the relationship between skeletal MM and clinical outcome was described in 2020, when Uojima et al [ 37 ] demonstrated that low MM was significantly associated with worse time to treatment failure and worse OS. Thereafter, two reports were published at the same time in which skeletal muscle depletion was not found associated with OS, unlike in a previous report [ 17 , 18 ]. In contrast, Hiraoka et al [ 38 ] recently reported that low MM was a significant prognostic factor.…”
Section: Impact Of Skeletal MM On Survival Among Patients Treated Wit...mentioning
confidence: 96%
“…We collected four articles in which both HGS and MM were evaluated in patients with HCC [14,17,18] or LC/ Liver Cancer 2022;11:329-340 DOI: 10.1159/000522389 HCC [16]. We divided the patients into four groups according to the JSH criteria [7].…”
Section: Relationship Between Hgs and Skeletal MMmentioning
confidence: 99%
See 3 more Smart Citations